Impact of probiotics on weight loss, glucose and lipid metabolism in overweight or obese women: A meta-analysis of randomized controlled trials - Ning Cao; Feiyan Zhao; Lai-Yu Kwok; Huan Wang; Zhihong Sun (Current Research in Food Science)
Our meta-analysis aimed to assess the effectiveness of probiotics in weight loss and glucose and lipid metabolism in overweight or obese women. PubMed, EMBASE, Cochrane Library, and Web of Science were used from inception until March 2024 to identify randomized controlled trials (RCT's) literature. Finally, 11 RCTs were included. Following critical appraisal, a meta-analysis was conducted using the fixed effects model and the random effects model found that probiotic consumption significantly decreased waist circumference (WC) (SMD = −0.39 cm, 95% CI: −0.60, −0.18 cm, P < 0.00001, I2 = 33%), insulin (SMD = −0.45 mcU/ml; 95% CI: −0.72, −0.18 mcU/ml; P = 0.04, I2 = 40%) and low-density lipoprotein cholesterol (LDL-C) levels (SMD = −0.51 mmol/L; 95% CI: −0.92, −0.11 mmol/L; P = 0.02, I2 = 75%) in overweight or obese women. Moreover, subgroup analyses revealed that the effects of probiotic supplementation were significantly influenced by the intervention duration and diet and/or exercise intervention. This meta-analysis suggested that probiotic supplementation has a moderate and statistically significant effect on weight loss and glucose and lipid metabolism in overweight and obese women.